The Study of Perception of Lexical Synonymy by Educable Children with Intellectual Disability Compared to Typically Developing Children - Abbas Ali Ahangar; Mehrdad Mazaheri; Mohaddeseh Soltaninezhad (Vesnu Publications, 2017)
Introduction: Synonymy occurs when two words have a similar meaning. Language perception is superior to language production. Moreover, considering that, due to some mental problems and low IQ, intellectually disabled children suffer from some difficulties in language comprehension, conducting a research on the perception of synonymy can help these children in their language communication. Thus, the purpose of the present research was to examine and compare the perception of synonymy in educable children with intellectual disability and typically developing children. Materials and Methods: The present study was a casual-comparative research. The data used in this research were gathered using the researcher-made Perception of Synonymy Questionnaire. To this end, 15 educable children with intellectual disability from exceptional schools and 15 typically developing children from ordinary schools of Jiroft, Iran, were asked to complete this questionnaire. The independent t-test was used to investigate and analyze the hypothesis of the present research and MANOVA was used to compare the perception of different kinds of synonymy. Results: The result of independent t-test showed that there was a significant difference between the mean of synonymy perception in educable children with intellectual disability and typically developing children (P < 0.05). Conclusion: Educable children with intellectual disability had difficulty in the perception of synonymy compared to typically developing children. However, the results of the present study showed no difference between educable children with intellectual disability and typically developing children in the understanding of two synonymous words belonging to different dialects and two synonymous words belonging to different languages.